Who Stops Drinking Alcohol in Russia? - Yana Roschina; Yulia Belova (Journal of Economic Sociology, 2024)
This paper, based on a longitudinal study, examines the factors of the transition to abstinence in Russia in the period from 2006 to 2020. The study draws on the database of the Russian Longitudinal Monitoring Survey, a series of representative surveys conducted by the Higher School of Economics for 20062020. Based on the results of binary logistic regression, several groups of factors were identified that influence the transition of Russians to abstinence in the year T + 1: older age, female gender, belonging to “Muslim ethnic groups”, living in cities of regional subordination and rural areas, pregnancy and childbirth by women, a decrease in per capita income for women, loss of employment status, self-assessment of health as deteriorating if the initial health assessment was as poor and very poor, self-assessment of health as improving compared to the initial health assessment as average, the presence of teetotalers in the family. Higher alcohol prices, other things being equal, increase the likelihood of men becoming abstainers more than twice. The most important factors for refusing to drink alcohol are natural - age and poor health. The presence of non-drinking family members contributes to the rejection of alcohol consumption, while excessive drinkers can have the opposite effect. An increase in the proportion of non-drinkers in the family and in society can set patterns for a sober lifestyle as a social norm. Promoting the value of health in society will help reduce alcohol consumption in the future.